(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
This article analyzes the terminology of natural sciences for students majoring in armachetics and biology, chemistry, which is currently emerging in each field due to the demand for foreign languages in their field, and offers suggestions for problems in teaching.